2011
DOI: 10.1007/s11144-011-0289-0
|View full text |Cite
|
Sign up to set email alerts
|

Substituted N-hydroxyphthalimides as oxidation catalysts

Abstract: A series of substituted N-hydroxyphthalimides (NHPI) with electronwithdrawing groups (4-C(O)OH, C=O) and an electron-donating group (4-C(CH 3 ) 3 ) were investigated as catalysts for cumene oxidation. The initial reaction rates, measured by the oxygen uptake, conversion of substrate and yield of oxidation products are discussed. The catalytic activity of oxidation rate enhancement of NHPI derivatives in acetonitrile follows the order 4-tert-BuNHPI [ NHPI [ 4-carb-NHPI [ NDHPI [ NAPI. NMPT, trityl-NPI and NHPLI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 23 publications
1
10
0
1
Order By: Relevance
“…This study complements the papers published thus far on the oxidation of isopropylarenes in the presence of NHPI [6][7][8][9][10][11][12] with respect to the range of the influence of temperature and the electron-donating substituents (methoxy, phenyl) on the course of the reaction as well as catalyst recovery and air application. The oxidation of hydrocarbons 2, 4 and 7 in the presence of NHPI to hydroperoxides are reported for the first time.…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…This study complements the papers published thus far on the oxidation of isopropylarenes in the presence of NHPI [6][7][8][9][10][11][12] with respect to the range of the influence of temperature and the electron-donating substituents (methoxy, phenyl) on the course of the reaction as well as catalyst recovery and air application. The oxidation of hydrocarbons 2, 4 and 7 in the presence of NHPI to hydroperoxides are reported for the first time.…”
Section: Introductionsupporting
confidence: 64%
“…The oxidation processes of isopropylaromatic hydrocarbons to hydroperoxides, as recently shown, can be catalyzed by N-hydroxyphthalimide (NHPI) [4][5][6][7][8][9][10][11] as well as its derivatives [12]. Literature data concerning the NHPI-catalyzed oxidation of isopropylarenes are collected in Table 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike initiator radicals involved only in the initial stages of the radical-chain process, the PINO radical takes part in the propagation stage (see Scheme ) and its structure has a significant impact on the oxidation process. For example, the introduction of various electron-withdrawing or -donor substituents into the benzene ring affects the persistence and reactivity of PINO radicals . Nevertheless, as far as we know, a systematic study of the influence of the PINO radicals’ structure on their persistence has not been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…However, Lanzalunga et al has shown that the rate of oxidation of 1-(4methoxyphenyl)ethanol is possible to increase by introducing electron-withdrawing substituents in NHPI aryl ring, and therefore, the reactivity order parallels the increase of OH BDE in the substituted NHPIs [19]. The effect of the electron-withdrawing substituents on the aromatic ring of NHPI and the stability of the transition state after hydrogen abstraction reaction by the PINO radical was also discussed by others [20][21][22]. After getting positive effects by using the fluorinated alkyl chain in NHPI, our next aim was to investigate the catalytic activity of another lipophilic NHPI derivative by introducing four electronegative fluorine atoms directly in the aryl ring of NHPI.…”
Section: Egyptian Journal Of Chemistrymentioning
confidence: 99%